Oil cooler partial shipment system - CHEN LEI; SHI SHENGXIANG; ZHU WEI; ZHOU YANLONG; PING ZHIQIAN; ZHANG JUNXIONG (2015)
The utility model relates to an oil cooler partial shipment system, the characteristic is: including end to end's the forefront body, the second -line body, the third wire body and the fourth wire body, arrange a plurality of trays on the forefront body, the second -line body, the third wire body and the fourth wire body, set up half special automatic clamp of oil cooler on the tray, the forefront body sets up first station, sets up the second station at the second -line body, sets up the third station at the third wire body, sets up the fourth station at the fourth wire body, the position that hangs of oil pressure pulse spanner and oil pressure pulse rifle is installed respectively to first station, second station, third station and fourth station, installs the button box that is used for controlling the tray operation respectively at first station, second station, third station and fourth station, equipment at quarter is beaten to the cold ware part leak test check out test set of one side mounting plate and the digital bar code of fourth station. The utility model provides an oil cooler assembly beat is low, the percent of automatization is low, the high problem of assembly fault rate.